Risk Factors and Outcome Analysis in Children with Carbon Monoxide Poisoning - Yu-Ching Chang; Hao-Yuan Lee; Jing-Long Huang; Cheng-Hsun Chiu; Chyi-Liang Chen; Chang-Teng Wu (Elsevier, 2017)
Carbon monoxide (CO) poisoning is one of the common causes of poisoning in patients and can result in significant morbidity and mortality. However, few studies have focused on the pediatric group. Methods: We retrospectively reviewed children (age < 18 years) with CO poisoning from nonfire accidents at a tertiary medical center in Taiwan from 2002 to 2010. We analyzed the patients' characteristics, management, and outcome; compared the data of patients who received hyperbaric oxygen (HBO) to those who received normobaric oxygen (NBO) therapy; and identified the ri0sk factors for patients who developed delayed neurological sequelae (DNS) or permanent neurological sequelae (PNS). Results: A total of 81 children were enrolled. The annual case number increased from five cases in 2002 to 20 in 2010, particularly during the cold months (December to February). The most common source of exposure was an indoor heating system (54.3%). The most common presenting symptoms were vomiting (32.1%) and consciousness changes (30.9%). HBO treatment tended to be administered to patients with a higher initial COHb (%) (p < 0.001), an initial Glasgow coma scale change (p < 0.001), and admission to the hospital (p = 0.002). After multivariate analysis, treatment in the intensive care unit because of prolonged loss of consciousness (p = 0.002) was the only independent risk factor for patients with DNS; only rescue by a ventilator (p < 0.001) was an independent risk factor for patients with PNS. In comparison to the NBO therapy, HBO treatment did not show benefit or harm to patients according to the incidence of inducing DNS or PNS after multivariate analysis. Conclusion: For those with treatment in the intensive care unit because of prolonged loss of consciousness and rescue by a ventilator, special attention should be given and follow-up should be performed to determine whether DNS or PNS occurs, particularly epilepsy and cognitive deficits.